Reconstructive and renewing operations results at locally spread extracerebral tumors of facial and cerebral cranial - Zozulya, Yu. A.; Vysotskiy, N. S.; Kvasha, M. S.; Kondratyuk, V. V.; Sambor, V. K. (Ukrainian Neurosurgical Journal, 2010)
On the base of 54 cases analysis the questions of renewing treatment optimization at patients with locally spread extrecerebral tumors were considered. The role of reconstructive and renewing operations was shown depending on tumor localization, size and growth characteristics and also radiotherapy and hormonal treatment in complex renewing treatment. The rational complex approach to renewing measures application is a factor of treatment efficiency increasing and satisfactory quality of life providing at patients with locally spread extracerebral tumors.